VALUE-BASED GLOBAL LEADERSHIP MODEL, “ING NGARSA SUNG TULADHA”: A LITERATURE REVIEW OF THE RELEVANCE OF KI HAJAR DIWANTARA’S THOUGHTS IN THE GLOBAL ERA - Ahmad Suyanto; Vita Fitriatul Ulya; Ganes Gunansyah; Neni Mariana (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
The glocalization of education presents a paradox between global standardization and the preservation of local identity in schools. Elementary education leadership is required to be adaptive to global dynamics without losing local cultural roots. This study aims to reconstruct a glocal leadership model based on the value of ing ngarsa sung tuladha in the thoughts of Ki Hajar Dewantara through a library research approach. Primary data were obtained from 25 reputable international and national journal articles indexed Q1, Q2, Sinta 1, Sinta 2 which were analyzed using thematic analysis and conceptual synthesis. The results of the study indicate that Ki Hajar Dewantara's exemplary principles have epistemological compatibility with the concept of glocalization which emphasizes the integration of global and local values in educational leadership practices. This study produces a Glocal leadership model GLOKADIG that integrates humanist digital exemplary behavior, value-based adaptive leadership, and glocal community involvement. Keywords: Glocalization; Educational Leadership; Ing Ngarsa Sung Tuladha; Ki Hajar Dewantara; Digital Role Model.   Abstrak Glokalisasi pendidikan menghadirkan paradoks antara standarisasi global dan pelestarian identitas lokal di sekolah. Kepemimpinan pendidikan dasar dituntut adaptif terhadap dinamika global tanpa kehilangan akar budaya lokal. Penelitian ini bertujuan merekronstruksi model kepemimpinan glokal berbasis nilai ing ngarsa sung tuladha dalam pemikiran Ki Hajar Dewantara melalui pendekatan penelitian kepustakaan. Data primer diperoleh dari artikel jurnal internasional dan nasional bereputasi yang berjumlah 25 artikel jurnal terindeks Q1, Q2, Sinta 1, Sinta 2 yang dianalisis menggunakan analisis tematik dan sintesis konseptual. Hasil kajian menunjukkan bahwa prinsip keteladanan Ki Hajar Dewantara memiliki kesesuaian epistemologis dengan konsep glokalisasi yang menekankan integrasi nilai global dan lokal dalam praktik kepemimpinan pendidikan. Penelitian ini menghasilkan model kepemimpinan Glokal GLOKADIG yang mengintegrasikan keteladanan digital humanis, kepemimpinan adaptif berbasis nilai, dan keterlibatan komunitas glokal. Kata kunci: Glokalisasi; Kepemimpinan Pendidikan; Ing Ngarsa Sung Tuladha; Ki Hajar Dewantara; Keteladanan Digital.